Efficient Ideal Algorithm for Task Scheduling in Cloud Computing - M K Kanna Babu, A; Sree Latha, M (International Journal of Engineering and Technology, 2018)
Present days cloud computing is one of the best raising technologies in distributed computing sectors which permits pays in line with model as per customer demand and requirements.Cloud includes a set of virtual machines which incorporates each persistent andcomputational facility. Providing efficient access of any data to the remote area through network is the primary motto of the cloud computing. Day by day cloud is facing many demanding situations. In which it is facing scheduling is the key one. The process through which the task can be done in certain order via pc device is called scheduling. The word scheduling defines different package of rules for controlling the task order for running the known job through network via computer machines. An awesome scheduler adapts the strategy of scheduling consistent with converting execution of job to sort of different tasks. In research paper we presented, data control of different virtual machines in cloud computing is the new target to the researchers. Algorithms of different tasks scheduling plays an essential and important role for solving some problems. The intention of the scheduling is running of different tasks successfully with in less time and accuracy.And we discussing about various components that cloud computing depends like CPU usage, Load balancing, and Time.Â Â